Tax policy of Serbia in the function of developing the economic system - Jugoslav Anicic; Marko Laketa; Branka Radovic; Dragan Radovic; Luka Laketa (UTMS Journal of Economics, 2012)
Global mobility of capital and labour impose the issue of optimal tax structure of all countries. In some countries, direct taxes on income and profits are still dominant, while in other the main source of tax incomes are indirect taxes, primarily value added tax (VAT). Tax system of Serbia is specific for its big burdens for work, and smaller burden of profits and property in relation to EU countries. For long-term sustainable economic growth, among other things, more efficient tax system is required. Tax policy should contribute to elimination of essential macroeconomic imbalances of Serbian economy - high unemployment rate and high foreign trade deficit, without endangering international competitiveness of a company and favourable economic environment.
Keywords: H20; R58; 330; tax system; tax policy; economic system; competitiveness